2022
DOI: 10.1021/acschembio.2c00286
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomic Profiling Reveals the Mechanism of Bile Acid Tolerance in Bacteria

Abstract: Bile acids (BAs) are a class of endogenous metabolites with important functions. As amphipathic molecules, BAs have strong antibacterial effects, preventing overgrowth of the gut microbiota and defending the invasion of pathogens. However, some disease-causing pathogens can survive the BA stress and knowledge is limited about how they develop BA tolerance. In this work, we applied a quantitative chemoproteomic strategy to profile BA-interacting proteins in bacteria, aiming to discover the sensing pathway of BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Next, we performed enzyme kinetics analysis of the deconjugation reaction. TLCA of increasing concentrations (1,5,10,20,50,100,200, 500 mM) were incubated with 100 nM BSH for 1 min. The input of TLCA and production of LCA were examined by LC-MS (Fig.…”
Section: Biochemical Activity Of E Faecium Bile Salt Hydrolase In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we performed enzyme kinetics analysis of the deconjugation reaction. TLCA of increasing concentrations (1,5,10,20,50,100,200, 500 mM) were incubated with 100 nM BSH for 1 min. The input of TLCA and production of LCA were examined by LC-MS (Fig.…”
Section: Biochemical Activity Of E Faecium Bile Salt Hydrolase In Vitromentioning
confidence: 99%
“…18 Of note, photoaffinity reporters were developed for primary bile acid cholic acid and enabled the identification of cholic acidbinding proteins in mammalian cell lines 19 and E. coli. 20 In addition, our chemoproteomic analysis in Salmonella revealed anti-infective bile acids such as chenodeoxycholic acid can bind and inactivate a transcriptional regulator of Salmonella virulence HilD. 21 Furthermore, chemical proteomic analysis of bile acid targets in Clostridium difficile showed that lithocholic acid (LCA) can bind and modulate the function of a stress response transcriptional regulator BapR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the identified proteins, 265 of them, including some known cholesterol-binding proteins and processing enzymes, were shown to be sensitive to cholesterol competition and selective for trans -sterol over the nonsteroidal neutral lipid probe ( N -palmitoylethanolamine-diazirine-alkyne). The Lei and Wang groups jointly reported a bile acid (BA) based A f BP (CA) with an alkyne and a diazirine installed at the C24 and C3 positions, respectively (Figure G). , Over 600 BA-interacting protein targets were subsequently identified in mammalian proteomes . Furthermore, a histidine kinase (EnvZ) was revealed to cause BA tolerance in bacteria …”
Section: Photolabeling Group Located At the Lipid Hydrophobic Partmentioning
confidence: 99%
“…The Lei and Wang groups jointly reported a bile acid (BA) based A f BP (CA) with an alkyne and a diazirine installed at the C24 and C3 positions, respectively (Figure G). , Over 600 BA-interacting protein targets were subsequently identified in mammalian proteomes . Furthermore, a histidine kinase (EnvZ) was revealed to cause BA tolerance in bacteria …”
Section: Photolabeling Group Located At the Lipid Hydrophobic Partmentioning
confidence: 99%